Pontryagin's minimum principle-based real-time energy management strategy for fuel cell hybrid electric vehicle considering both fuel economy and power source durability. (15th August 2020) - Song, Ke; Wang, Xiaodi; Li, Feiqiang; Sorrentino, Marco; Zheng, Bailin
Abstract: This paper presents a real-time and approximately optimal energy management strategy (EMS) based on Pontryagin's minimum principle (PMP), considering both fuel economy and power source durability. To develop the target strategy, performance degradation models are built for two power sources: a proton exchange membrane fuel cell and a lithium ion battery. This study provides an online co-state updating method for uncertain driving cycles. The method allows the battery's state of charge to be controlled within a certain range and determines the nearly optimal hydrogen consumption. Furthermore, by incorporating a fuel cell power variation limiting factor with a weight coefficient into the PMP to suppress power changes, the durability of the fuel cell can be improved. The average daily operating cost (calculated based on the fuel consumption and power source degradation) is used to evaluate the trade-off between fuel economy and power source durability. Simulation results show that the fuel cell durability is improved with a slight increase in fuel consumption and battery degradation, and that the average daily operating cost is effectively reduced. A comparison with the results obtained by adopting a rule-based EMS and a dynamic programming-based EMS indicate the superiority of the proposed EMS. Highlights: A co-state updating method is proposed to realise online implementation of PMP. Hamiltonian function is rewrite to take power sources durability into account. Suboptimal real-time PMP-based energy management strategy is developed. Average daily operating cost function is devised for assessing different EMSs.